Тихий ангел: [рассказы] / Наталья Нестерова - Нестерова Наталья Владимировна (Сарафанное радио, 2008)
Экземпляры: аб. (2010) / Инвентарный номер: 53649 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Н 56 / ГРНТИ: 17.82.32 / ББК: 84(2Рос=Рус)6-44